Gestión de Residuos en los Laboratorios de Química - Loayza Pérez, Jorge Eduardo (2005)
The educative institutions and the companies of services that count on compatible laboratories of chemistry, in order to bring chemical experiences of laboratory or analyses as a part of a service to third, require, like the productive companies, of an appropriate management and handling of their chemical wastes.